2020
DOI: 10.3390/vision4040045
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Corneal Thickness, Densitometry and Curvature on Intraocular Pressure Measurements Obtained by Applanation, Rebound and Dynamic Contour Tonometry

Abstract: Evaluate the effect of corneal thickness, densitometry and curvature on intraocular pressure (IOP) measurements obtained by Goldmann applanation tonometry (GAT), non-contact tonometry (NCT), rebound tonometry (RT), and dynamic contour tonometry (DCT). A cross-sectional prospective study involving 40 participants was performed. Corneal measurements were obtained using Pentacam (Oculus GMbH, Wetzlar, Germany), densitometry was measured at annuli of 0–2, 2–6, 6–10 and 10–12 mm. The relationship between corneal th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…The question arises, whether the reduction was related to the surgery itself or it was a result of 6-months presence of intraocular silicon oil tamponade or both. Current studies suggest that in eyes with chronically elevated IOP, CCT is significantly reduced, what can be consistent with long-term increase in IOP related to silicon oil tamponade lasting 6-months in our patients 23 . The pathomechanism of CCT changes in patients with elevated IOP is not entirely clear 24 .…”
Section: Discussionsupporting
confidence: 90%
“…The question arises, whether the reduction was related to the surgery itself or it was a result of 6-months presence of intraocular silicon oil tamponade or both. Current studies suggest that in eyes with chronically elevated IOP, CCT is significantly reduced, what can be consistent with long-term increase in IOP related to silicon oil tamponade lasting 6-months in our patients 23 . The pathomechanism of CCT changes in patients with elevated IOP is not entirely clear 24 .…”
Section: Discussionsupporting
confidence: 90%
“…Ethnicity 6 , 20 , 24 , 43 and the measurement method to determine IOP 44 50 are known factors that influence IOP results: CCT does not seem to interfere with IOP measurements taken by Pascal dynamic contour tonometry. 47 Abah revealed a correlation between CCT and IOP using Perkins applanation tonometry, 5 whereas in the South African Eye Study this association was shown using rebound tonometry.…”
Section: Discussionmentioning
confidence: 99%
“…This restricted recruitment explains the large age range which could interfere with results, although the variable age was included in our analysis. A further limitation of the present study was that we did not examine possible effects of potentially relevant factors, including axial length,19 corneal characteristics such as corneal curvature,9 corneal diameter9 and corneal densitometry20 or effects of glaucoma treatment,21,22 and surgeries23 on the differences in IOP observed with different instruments.…”
Section: Discussionmentioning
confidence: 98%